2015
DOI: 10.1016/j.cell.2015.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Foods as Experimentally Tractable Microbial Ecosystems

Abstract: Microbial communities of fermented foods have provided humans with tools for preservation and flavor development for thousands of years. These simple, reproducible, accessible, culturable, and easy-to-manipulate systems also provide opportunities for dissecting the mechanisms of microbial community formation. Fermented foods can be valuable models for processes in less tractable microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
240
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(251 citation statements)
references
References 51 publications
5
240
0
6
Order By: Relevance
“…These studies provided an in‐depth analysis of the cheese maturation process and allowed to better understand the metabolic activities of the different community members and their possible interactions. Indeed, cheese microbial communities were proposed as simplified model to study both microbial assembly and metabolism (as affected by abiotic factors), providing a possible interesting model for understanding microbial dynamics in more complex environments (Wolfe and Dutton, 2015). In a recent example, the evolution of bacterial activities during manufacturing and ripening of a traditional cheese made with an undefined starter was monitored by metatranscriptomics highlighting how to manipulate microbial gene expression through modifications of the process parameters (De Filippis et al ., 2016a).…”
Section: Exploring Microbial Functions Directly In Foodmentioning
confidence: 99%
“…These studies provided an in‐depth analysis of the cheese maturation process and allowed to better understand the metabolic activities of the different community members and their possible interactions. Indeed, cheese microbial communities were proposed as simplified model to study both microbial assembly and metabolism (as affected by abiotic factors), providing a possible interesting model for understanding microbial dynamics in more complex environments (Wolfe and Dutton, 2015). In a recent example, the evolution of bacterial activities during manufacturing and ripening of a traditional cheese made with an undefined starter was monitored by metatranscriptomics highlighting how to manipulate microbial gene expression through modifications of the process parameters (De Filippis et al ., 2016a).…”
Section: Exploring Microbial Functions Directly In Foodmentioning
confidence: 99%
“…This has yielded exciting results, with B. subtilis biofilm formation and properties (Bais, 2004) being studied in the soil, on plant roots in the lab, naturally induced by the plants' polysaccharides (Beauregard et al, 2013). Similarly, both synthetic communities constructed from known microbial species (Hekstra and Leibler, 2012;van Gestel et al, 2014) and microcosm communities made from environmental samples (Wolfe and Dutton, 2015) have been shown to reveal essential characteristics of microbial ecology (for a review, see Widder et al, 2016).…”
Section: Future Directionsmentioning
confidence: 99%
“…Preliminary studies have shown that DNA sequencing can answer various food-related applications including distinguishing morphologically similar poisonous and edible mushrooms, detecting the accumulation of pathogenic microbes in meat, tracing the fermentation of cheeses, identifying hidden traces of allergens, and even predicting the ripening time of avocados (Dopico et al 1993;Galimberti et al 2013;Dugat-Bony et al 2015;Wolfe and Dutton 2015). As such, sequencing sensors can be a highly flexible backend to monitor various issues in the food supply chain.…”
Section: Food Industrymentioning
confidence: 99%